Efek Terapeutik Analog Somatostatin dalam Menghambat Perkembangan Autosomal Dominant Polycystic Kidney Disease - Sitompul, Irvin Rembrant Holleritz; Putri, Grasella Angelika; Laksmi, Purwita Wijaya (Jurnal Penyakit Dalam Indonesia, 2024)
Autosomal Dominant Polycystic Kidney Disease (ADPKD) is a hereditary disorder characterized by formation and progressive growth of cysts in the kidneys and other organs such as liver, spleen, and pancreas. Recent advances have led to possibilities to target the main cause of cyst growth, cAMP. Somatostatin targets cAMP and inhibits its production directly and indirectly in kidney and liver, which might potentially prevent renal and liver cyst progression in ADPKD. This report aims to evaluate the effectiveness of somatostatin analogue therapy in slowing disease progression in ADPKD patients, according to the latest evidence. A literature search was conducted on five databases, namely the Cochrane Library, EBSCO, Embase, ProQuest, and PubMed/MEDLINE. Selected articles are screened for duplication, title and abstract, as well as based on eligibility criteria. The selected articles were then critically appraised using the Oxford Center for Evidence Based Medicine (CEBM) critical appraisal tools for therapeutic study and systematic review as a guide. The systematic search resulted in one meta-analysis assessing the effectiveness of somatostatin analogues in ADPKD patients in terms of Total Kidney Volume (TKV), Total Liver Volume (TLV), and eGFR. This article analyzed 10 RCTs with a total sample size of 854 subjects. This study showed that somatostatin analogue is associated with lower TLV (%TLV) growth (MD -6.37%; 95% CI -7.90 to -4.84; p<0.001; I2 = 14%), and lower TKV (%TKV) growth rate (MD -3.66%; 95% CI -5.35 to -1.97; p<0.001; I2 = 56%). However, it was not associated with eGFR decline (MD -0.96 mL/min/1.73m2; 95% CI -2.38 to 0.46; p = 0.19; I2 = 74%). Adverse effects were mainly gastrointestinal tract symptoms, and approximately 15% of test subjects administered with somatostatin analogue permanently discontinued the drug. Somatostatin analogue therapy has benefit in slowing TLV and TKV growth which outweigh the cost and risk of therapy. In conclusion, somatostatin can be recommended as therapy in ADPKD patients presenting with both kidney and liver cyst.